PENGARUH PENAMBAHAN ENZIM BROMELIN DAN TITIK KRITISNYA DALAM PEMBUATAN TAHU SUSU - Gesa Aldin Barqin, (Jurnal Ilmiah Pangan Halal, 2021)
Repeated processing of tofu will cause saturation in consumption, to anticipate this, innovation in the food sector is needed, one of which is the manufacture of milk tofu. Milk processing can produce added value and a longer shelf life. The process of making tofu milk is done by clumping. The clumping can use natural coagulation materials enzymatically, namely the bromelain enzyme. Bromelain enzyme can be obtained from pineapple fruit. Pineapple have several varieties, the differences in these varieties will affect the levels of the enzyme bromelain contained so that in the manufacture of milk tofu cannot use the same formula for all varieties. The critical point in the process of making milk tofu is at temperature, because the activity of the bromelain enzyme will increase to a temperature limit of 50℃, after that its activity will decrease, thus the bromelain enzyme is no longer active at high temperatures because it is damaged. In the final product, the addition of pineapple bromelain enzyme in the manufacture of milk tofu will affect the protein content, color, taste, and texture.